Between expediency and creativity the choice for Filipinos - Gonzalez, N.V.M (Danyag :the UPV journal of humanities and social sciences)
"The essay is an adaptation of a talk given by the author at a recent colloquium sponsored by the Program for Southeast Asian Studies, and the Philippine Association for Graduate Education at State University of Arizona, Tempe, Arizona. The same was shared shortly after before an audience of Filipinos and Filipino Americans at the Philippine Consulate, Los Angeles, CA."